Meeting the Needs of People With Severe Quadriplegia in the 21st Century: The Case for Implanted Brain–Computer Interfaces. - Sawyer, Abbey; Cooke, Lily; Breyman, Erica; Spohn, Steve; Edelman, Sandy; Saravanan, Krisha; Putrino, David (Neurorehabilitation & Neural Repair, 2024)
Background: In recent decades, there has been a widespread adoption of digital devices among the non-disabled population. The pervasive integration of digital devices has revolutionized how the majority of the population manages daily activities. Most of us now depend on digital platforms and services to conduct activities across the domains of communication, finance, healthcare, and work. However, a clear disparity exists for people who live with severe quadriplegia, who largely lack access to tools that would enable them to perform daily tasks digitally and communicate effectively with their environment. Objectives: The purpose of this piece is to (i) highlight the unmet needs of people with severe quadriplegia (including cases for medical necessity and perspectives from the community), (ii) present the current landscape of assistive technology for people with severe quadriplegia, (iii) make the case for implantable BCIs (how they address needs and why they are a good solution relative to other assistive technologies), and (iv) present future directions. Results: There are technologies that are currently available to this population, but these technologies are certainly not usable with the same level of ease, efficiency, or autonomy as what has been designed for the non-disabled community. This hinders the ability of people with severe quadriplegia to achieve digital autonomy, perpetuating social isolation and limiting the expression of needs, opinions, and preferences. Conclusion: Most importantly, the gap in digital equality fundamentally undermines the basic human rights of people with severe quadriplegia.